Pengaruh Pendampingan Keluarga Terhadap Kecemasan Belajar Anak pada Pembelajaran Jarak Jauh Selama Pandemi Covid-19 - Putri, Sandra Febby Eka; Abidin, Zaenal; Ramadhanintyas, Karina Nur; Ratnawati, Riska (Edusia: Jurnal Ilmiah Pendidikan Asia, 2021)
Learning anxiety is an excessive feeling of being afraid of threats or felt during distance learning. In overcoming children's anxiety, one of the assistance efforts made is family support. Family support is an act of assisting to meet the needs and problem solving of children in order to support the optimization of children's development. In this study, researchers used quantitative descriptive as an approach. The research method used is an analytic survey while the type of research is cross sectional. In analyzing the data, researchers used univariate as a measuring tool and the Chi-Square test as bivariate. The population of elementary school children in grades 4-6 is 60 respondents and the sample is 60 respondents. The results of the bivariate test showed that there was a significant relationship between the independent variables, that the p value was 0.044 (p < 0.05), which means that there is an influence between family support and children's learning anxiety. In this study, the study analyzed that the Chi-Square test had 2 (two) most influential variables, namely family support and children's learning anxiety. The conclusion of this study is that there is a significant relationship between family support and children's learning anxiety. From this research, it is expected that children will learn with others so that children do not experience anxiety.